Nano silicon-graphite composite negative electrode material with carbon coating and aluminum metaphosphate composite modification layer on surface, application of nano silicon-graphite composite negative electrode material and button lithium ion battery
By performing carbon coating and aluminum metaphosphate composite modification on the surface of nano-silicon-graphite composite anode material, the powdering problem caused by volume changes during the electrochemical cycle is solved, and the cycle life and capacity retention rate of the material are significantly improved. .
Patent Information
- Application Number
- CN202411581630.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-29
- Publication Date
- 2025-02-14
AI Technical Summary
The nano-silicon and graphite composite anode material has particles powdered due to volume expansion and contraction during the electrochemical cycle, resulting in capacity loss and cycle life attenuation.
Nanosilicon-graphite composite anode material using surface carbon coating and aluminum metaphosphate composite modified layer, thereby enhancing conductivity and insulating electrolyte erosion through carbon coating, aluminum metaphosphate enhances the peel strength of the cladding layer and forms a stable SEI. membrane.
The cycle life and capacity retention rate of nano-silicon-graphite composite anode material is significantly improved, the impact of volume changes on the material is alleviated, and the consumption of electrolyte is reduced.
Smart Images

Figure BDA0005123268220000081 
Figure HDA0005123268230000011 
Figure HDA0005123268230000012
Abstract
Description
[0001] This application is a divisional application with an application date of April 29, 2022, application number 202210473280.2, and invention name "Nano-silicon-graphite composite negative electrode material with carbon coating and aluminum metaphosphate composite modification layer on the surface and preparation method thereof". Technical Field
[0002] The invention relates to the technical field of electrochemical power sources, and in particular to a nano silicon-graphite composite negative electrode material with a carbon coating and an aluminum metaphosphate composite modification layer on the surface, an application thereof, and a button-type lithium ion battery. Background Art
[0003] Silicon inserts lithium by forming lithium-silicon alloy with lithium. The process of inserting lithium is accompanied by huge volume expansion, and the process of removing lithium and de-alloying is accompanied by drastic volume contraction. This volume change is as high as 300%, which can easily cause silicon material to pulverize, seriously affecting the cycle stability. By preparing nano-silicon powder of appropriate particle size, the particle pulverization of silicon materials during the electrochemical cycle can be effectively solved. However, the huge volume change effect of nano-silicon materials after lithium insertion still exists. After repeated volume expansion and contraction of the electrode, the particles will still lose electrical contact and pulverize, resulting in capacity loss and cycle life decay. Using existing mature commercial graphite-based negative electrode materials as the basic skeleton composite nano-silicon materials to make up for the inherent shortcomings of silicon-based materials and obtain new composite negative electrode materials whose specific capacity and cycle life meet the requirements of lithium-ion battery negative electrode materials is an effective and feasible low-cost method.
[0004] However, after nano-silicon is compounded with graphite, the expansion and contraction rates of the two during lithium insertion and extraction are inconsistent, which can easily lead to the nano-silicon particles losing electrical contact, resulting in capacity loss. At the same time, the SEI film formed on the surface is unstable and continuously consumes electrolyte, which hinders the lithium ion transmission of the battery, thereby causing the material cycle life to decrease. Furthermore, at this stage, the cycle life is mainly improved by nano-sizing silicon materials and compounding them with other materials. However, after nano-sizing silicon materials, the specific surface area is large, and the surface is easily corroded by the electrolyte. Although lithium insertion expansion still exists after nano-sizing silicon materials, further surface modification is required. The present invention obtains a nano-silicon-graphite composite negative electrode material with a long cycle life by performing carbon coating and metaphosphoric acid composite modification on the surface of the material in a simple and easy manner. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a nano silicon-graphite composite negative electrode material with a carbon coating and an aluminum metaphosphate composite modification layer on the surface, its application, and a button lithium ion battery. In the present invention, the presence of the composite modification layer not only has the effect of traditional carbon coating, such as improving the conductivity of silicon materials, isolating the corrosion of silicon materials by electrolytes, and alleviating volume expansion, but also the aluminum metaphosphate is dispersed in the coating layer to enhance the peeling strength of the coating layer, which can better adapt to the volume change of the material; at the same time, the presence of aluminum metaphosphate helps to form a stable SEI film on the surface of the material, reduce the consumption of electrolytes, and obtain a higher cycle life.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface, wherein the negative electrode material is mainly prepared from the following components according to mass percentage:
[0008] 4-10wt.% of aluminum metaphosphate powder, 10wt.% of asphalt cracking carbon, 15wt.% of spherical nano silicon powder and 71-65wt.% of graphite powder.
[0009] Another technical purpose of the present invention is to provide a method for preparing the nano silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface, including a method and steps for preparing the surface carbon coating and the aluminum metaphosphate composite modification layer, the nano silicon-graphite composite material, and using the nano silicon-carbon composite material as a lithium ion battery; wherein the preparation method involved in the present invention is as follows:
[0010] First, nano silicon powder is added to deionized water for ultrasonic dispersion to obtain a uniform dispersion, and then graphite powder is added and ultrasonically stirred evenly, and then aqueous asphalt is added. After stirring and mixing evenly, it is spray dried. The dried powder is combined with metaphosphate for mechanical fusion, and finally transferred to a vacuum furnace for high-temperature carbonization to obtain a nano silicon-graphite composite negative electrode material with a carbon coating and an aluminum metaphosphate composite modification layer on the surface.
[0011] The specific steps include:
[0012] 1) adding spherical nano silicon powder according to the formula into deionized water and dispersing by ultrasonic stirring to obtain a spherical nano silicon powder dispersion;
[0013] 2) stirring the spherical nano-silicon powder dispersion of step 1) at high speed, first adding graphite powder according to the formula ratio, stirring and mixing for a certain period of time, then adding water-based asphalt, stirring at high speed to be uniform, and adding deionized water to control the solid content of the obtained dispersion to be within the range of 10 to 15 wt.%;
[0014] 3) spray drying the dispersion obtained in step 2) with a spray dryer, controlling the spray inlet temperature at 200-220° C. and the feed rate at 20-30 kg / h to obtain a dry powder;
[0015] 4) weighing aluminum metaphosphate powder according to the formula ratio, adding it to the dry powder in step 3), mixing evenly, adding it to a mechanical fusion machine for fusion, and obtaining a precursor with a layer of asphalt and aluminum metaphosphate modified on the surface;
[0016] 5) The precursor in step 4) is transferred into a vacuum furnace and carbonized at 800-1200° C. for 3-6 hours, then taken out, crushed and sieved to obtain a nano-silicon-graphite composite negative electrode material with a carbon coating and an aluminum metaphosphate composite modification layer on the surface.
[0017] It is worth noting that the present invention can well enhance the bonding strength between nano-silicon and graphite and improve the conductivity of silicon materials by modifying the carbon coating layer on the surface of nano-silicon-graphite composite negative electrode materials, and can well alleviate the volume expansion and stabilize the SEI film formed on the surface of the material by modifying the surface with aluminum metaphosphate. Based on the nano-silicon-graphite composite negative electrode material prepared by combining nano-silicon and graphite, the present invention enhances the conductivity of nano-silicon particles by surface carbon coating and aluminum metaphosphate composite modification layer, stabilizes the SEI film, and alleviates the volume change of the material to obtain a composite negative electrode material with a higher cycle life.
[0018] Compared with the prior art, the present invention discloses a nano silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface and a preparation method thereof, which has the following beneficial effects:
[0019] 1) The presence of the composite modification layer not only has the effects of traditional carbon coating, such as improving the conductivity of silicon materials, isolating the corrosion of silicon materials by electrolytes, and alleviating volume expansion, but also the aluminum metaphosphate dispersed in the coating layer enhances the peeling strength of the coating layer and can better adapt to the volume changes of the material.
[0020] 2) The presence of aluminum metaphosphate helps to form a stable SEI film on the surface of the material, reduce the consumption of electrolyte, and obtain a higher cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0022] Figure 1The invention discloses an energy spectrum analysis of a nano silicon-graphite composite negative electrode material with aluminum metaphosphate modified on its surface, which is prepared by the present invention.
[0023] Figure 2 The silicon-carbon composite materials prepared in Example 1 and Comparative Example 1 of the present invention are made into negative electrode sheets, which are then assembled into 2032 button batteries and tested to obtain a capacity retention rate curve. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Embodiment 1:
[0026] A method for preparing a nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface, specifically comprising the following steps:
[0027] 1) Weighing 450 g of spherical nano silicon powder, adding it into 27 kg of deionized water and dispersing it by ultrasonic stirring to obtain a spherical nano silicon powder dispersion;
[0028] 2) The dispersion of step 1) was stirred at high speed, and 1950 g of graphite powder was added at the same time, and the mixture was stirred and mixed thoroughly, and then 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) was added and mixed evenly to obtain a uniform slurry with a solid content of about 10 wt.%;
[0029] 3) spray drying the uniform slurry obtained in step 2) while ultrasonically stirring, controlling the inlet temperature of the sprayer at 220° C. and the feed rate at 30 kg / h to obtain a dry powder;
[0030] 4) Weighing 300 g of aluminum metaphosphate powder and the dry powder obtained in step 3) and adding them to a mechanical fusion machine, extruding and fusing at high speed for 20 minutes, to obtain a precursor with a surface coated with a layer of asphalt and modified with aluminum metaphosphate;
[0031] 5) transferring the precursor in step 4) into a vacuum furnace and carbonizing it at 800° C. for 3 h to carbonize the asphalt at high temperature, thereby obtaining a nano-silicon-graphite composite negative electrode material having a composite modification layer of about 10 wt.% asphalt cracking carbon and 10 wt.% aluminum metaphosphate on the surface;
[0032] The nano-silicon-graphite composite negative electrode material prepared in this embodiment was prepared into a negative electrode sheet and assembled into a 2032 button battery to test the cycle life. The material performance data is shown in Table 1, and the cycle life curve is shown in Figure 2 shown.
[0033] The test method for the battery cycle performance is as follows: first discharge to 0.01v at a current density of 100mA / g, then discharge to 0.005v at a current density of 10mA / g, let stand for 3 minutes, and then charge to 1.5v at a current density of 100mA / g, which is one cycle to test the cycle performance.
[0034] In addition, the nano-silicon-graphite composite negative electrode material with aluminum metaphosphate modified on the surface prepared by the present invention was subjected to energy spectrum analysis, as shown in the attached Figure 1 From the energy spectrum, it can be seen that the nano-silicon particles are dispersed on the surface of the graphite particles in the composite material, and the particles are combined into a whole through the carbon coating on the surface and the aluminum metaphosphate modification layer.
[0035] Example 2
[0036] A method for preparing a nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface, specifically comprising the following steps:
[0037] 1) Weighing 450 g of spherical nano silicon powder, adding it into 27 kg of deionized water and dispersing it by ultrasonic stirring to obtain a dispersion of spherical nano silicon powder;
[0038] 2) The dispersion of step 1) was stirred at high speed, and 2130 g of graphite powder was added at the same time, and the mixture was stirred and mixed thoroughly, and then 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) was added and mixed evenly to obtain a uniform slurry with a solid content of about 10 wt.%;
[0039] 3) spray drying the uniform slurry obtained in step 2) while ultrasonically stirring, controlling the inlet temperature of the sprayer at 200° C. and the feed rate at 30 kg / h to obtain a dry powder;
[0040] 4) Weighing 120 g of aluminum metaphosphate powder and the dry powder obtained in step 3) and adding them to a mechanical fusion machine, extruding and fusing at high speed for 20 minutes, to obtain a precursor coated with a layer of asphalt and modified with aluminum metaphosphate;
[0041] 5) transferring the precursor in step 4) into a vacuum furnace and carbonizing it at 800° C. for 6 h to carbonize the asphalt at high temperature, thereby obtaining a nano-silicon-graphite composite negative electrode material having a composite modified layer of about 10 wt.% asphalt cracking carbon and 4 wt.% aluminum metaphosphate on the surface;
[0042] Example 3
[0043] A method for preparing a nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface, specifically comprising the following steps:
[0044] 1) Weighing 450 g of spherical nano silicon powder, adding it into 17 kg of deionized water and dispersing it by ultrasonic stirring to obtain a dispersion of spherical nano silicon powder;
[0045] 2) The dispersion of step 1) was stirred at high speed, and 1950 g of graphite powder was added at the same time, and the mixture was stirred and mixed thoroughly, and then 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) was added and mixed evenly to obtain a uniform slurry with a solid content of about 15 wt.%;
[0046] 3) spray drying the uniform slurry obtained in step 2) while ultrasonically stirring, controlling the inlet temperature of the sprayer at 200° C. and the feed rate at 30 kg / h to obtain a dry powder;
[0047] 4) Weighing 300 g of aluminum metaphosphate powder and the dry powder obtained in step 3) and adding them to a mechanical fusion machine, extruding and fusing at high speed for 20 minutes, to obtain a precursor with a surface coated with a layer of asphalt and modified with aluminum metaphosphate;
[0048] 5) transferring the precursor in step 4) into a vacuum furnace and carbonizing it at 1000° C. for 6 h to carbonize the asphalt at high temperature, thereby obtaining a nano-silicon-graphite composite negative electrode material having a composite modification layer of about 10 wt.% asphalt cracking carbon and 10 wt.% aluminum metaphosphate on the surface;
[0049] Example 4
[0050] A method for preparing a nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface, specifically comprising the following steps:
[0051] 1) Weighing 450 g of spherical nano silicon powder, adding it into 22 kg of deionized water and dispersing it by ultrasonic stirring to obtain a dispersion of spherical nano silicon powder;
[0052] 2) The dispersion of step 1) was stirred at high speed, and 2010 g of graphite powder was added at the same time, and the mixture was stirred and mixed thoroughly, and then 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) was added and mixed evenly to obtain a uniform slurry with a solid content of about 12.2 wt.%;
[0053] 3) spray drying the uniform slurry obtained in step 2) while ultrasonically stirring, controlling the inlet temperature of the sprayer at 210° C. and the feed rate at 30 kg / h to obtain a dry powder;
[0054] 4) Weighing 240 g of aluminum metaphosphate powder and the dry powder obtained in step 3) and adding them to a mechanical fusion machine, extruding and fusing at high speed for 20 minutes, to obtain a precursor coated with a layer of asphalt and modified with aluminum metaphosphate;
[0055] 5) transferring the precursor in step 4) into a vacuum furnace and carbonizing it at 1200° C. for 3 h to carbonize the asphalt at high temperature, thereby obtaining a nano-silicon-graphite composite negative electrode material having a composite modified layer of about 10 wt.% asphalt cracking carbon and 8 wt.% aluminum metaphosphate on the surface;
[0056] Example 5
[0057] A method for preparing a nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface, specifically comprising the following steps:
[0058] 1) Weighing 450 g of spherical nano silicon powder, adding it into 27 kg of deionized water and dispersing it by ultrasonic stirring to obtain a dispersion of spherical nano silicon powder;
[0059] 2) The dispersion of step 1) was stirred at high speed, and 2070 g of graphite powder was added at the same time, and the mixture was stirred and mixed thoroughly, and then 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) was added and mixed evenly to obtain a uniform slurry with a solid content of about 10.4 wt.%;
[0060] 3) spray drying the uniform slurry obtained in step 2) while ultrasonically stirring, controlling the inlet temperature of the sprayer at 220° C. and the feed rate at 30 kg / h to obtain a dry powder;
[0061] 4) Weighing 180 g of aluminum metaphosphate powder and the dry powder obtained in step 3) and adding them to a mechanical fusion machine, extruding and fusing at high speed for 20 minutes, to obtain a precursor coated with a layer of asphalt and modified with aluminum metaphosphate;
[0062] 5) The precursor in step 4) is transferred into a vacuum furnace and carbonized at 1100°C for 4 hours to carbonize the asphalt at high temperature to obtain a nano-silicon-graphite composite negative electrode material having a surface modified layer of about 10 wt.% asphalt cracking carbon and 6 wt.% aluminum metaphosphate.
[0063] To further verify the superior effect of the present invention compared with the prior art, the inventors also conducted the following comparative experiments and performance tests, the specific contents of which are as follows:
[0064] Comparative Example 1
[0065] 1) Weighing 450 g of spherical nano silicon powder, adding it into 27 kg of deionized water and dispersing it by ultrasonic stirring to obtain a dispersion of spherical nano silicon powder;
[0066] 2) The dispersion of step 1) was stirred at high speed, and 1950 g of graphite powder was added at the same time, and the mixture was stirred and mixed thoroughly, and then 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) was added and mixed evenly to obtain a uniform slurry with a solid content of about 10 wt.%;
[0067] 3) spray drying the uniform slurry obtained in step 2) while ultrasonically stirring, controlling the inlet temperature of the sprayer at 220° C. and the feed rate at 30 kg / h to obtain a dry powder;
[0068] 4) The precursor in step 3) is transferred to a vacuum furnace for carbonization treatment at 800° C. for 3 h to carbonize the asphalt at high temperature to obtain a nano-silicon-graphite composite negative electrode material with only a carbon coating layer on the surface and no aluminum metaphosphate modification;
[0069] The nano-silicon-graphite composite negative electrode material without surface modification in Comparative Example 1 was assembled into a 2032 button-type battery to test the cycle life. The material performance data is shown in Table 1, and the cycle life curve is shown in Figure 2 shown.
[0070] Comparative Example 2
[0071] 1) Weighing 450 g of spherical nano silicon powder, adding it into 27 kg of deionized water and dispersing it by ultrasonic stirring to obtain a dispersion of spherical nano silicon powder;
[0072] 2) The dispersion of step 1) was stirred at high speed, and 1950 g of graphite powder was added at the same time, and the mixture was stirred and mixed thoroughly, and then 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) was added and mixed evenly to obtain a uniform slurry with a solid content of about 10 wt.%;
[0073] 3) spray drying the uniform slurry obtained in step 2) while ultrasonically stirring, controlling the inlet temperature of the sprayer at 220° C. and the feed rate at 30 kg / h to obtain a dry powder;
[0074] 4) The precursor in step 3) is transferred into a vacuum furnace and carbonized for 3 hours under vacuum conditions at 800° C. to carbonize the asphalt at high temperature to obtain a nano-silicon-graphite composite negative electrode material with no carbon coating layer on the surface and only aluminum metaphosphate modification;
[0075] The nano-silicon-graphite composite negative electrode material without surface modification in Comparative Example 2 was assembled into a 2032 button-type battery to test the cycle life. The material performance data are shown in Table 1.
[0076] Comparative Example 3
[0077] 1) Weighing 450 g of spherical nano silicon powder, adding it into 27 kg of deionized water and dispersing it by ultrasonic stirring to obtain a dispersion of spherical nano silicon powder;
[0078] 2) stirring the dispersion obtained in step 1) at high speed, adding 1950 g of graphite powder, stirring and mixing thoroughly to obtain a uniform slurry with a solid content of about 10 wt.%;
[0079] 3) spray drying the uniform slurry obtained in step 2) while ultrasonically stirring, controlling the inlet temperature of the sprayer at 220° C. and the feed rate at 30 kg / h to obtain a dry powder;
[0080] 4) transferring the precursor in step 3) into a vacuum furnace and carbonizing it at 800° C. for 3 h to obtain a nano-silicon-graphite composite negative electrode material having no carbon coating and no aluminum metaphosphate modification on the surface;
[0081] The nano-silicon-graphite composite negative electrode material without surface modification in Comparative Example 3 was assembled into a 2032 button-type battery to test the cycle life. The material performance data are shown in Table 1.
[0082] As can be seen from Table 1, the unmodified comparative example 3 has only 28.4% capacity retention after 300 cycles, the comparative example 1 modified with only the carbon coating layer has 70.7% capacity retention after 300 cycles, and the comparative example 2 modified with only aluminum metaphosphate has a capacity retention rate of 46.2% after 300 cycles. After carbon coating and aluminum metaphosphate composite modification, the cycle life of the material is significantly improved. After 300 cycles, the capacity retention rates of the samples of Examples 1 to 5 are 103.7%, 98.8%, 104.3%, 102.8% and 104.4%, respectively. Through comparative analysis, it can be found that the carbon coating and aluminum metaphosphate composite modification layer designed by the present invention can greatly improve the cycle life of the nano-silicon-graphite composite negative electrode material.
[0083] Table 1 Performance data of button-type lithium-ion batteries obtained in Examples 1 to 5 and Comparative Examples 1 to 3
[0084]
[0085] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface, characterized in that: The nano-silicon-graphite composite negative electrode material is prepared from the following components according to mass percentage: 6-10wt.% of aluminum metaphosphate powder, 10wt.% of asphalt cracking carbon, 15wt.% of spherical nano-silicon powder and 65-69wt.% of graphite powder; The method for preparing the nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface comprises the following steps: 1) adding spherical nano silicon powder according to the formula into deionized water and dispersing by ultrasonic stirring to obtain a spherical nano silicon powder dispersion; 2) stirring the spherical nano-silicon powder dispersion of step 1) at high speed, first adding graphite powder according to the formula ratio, stirring and mixing for a certain period of time, adding water-based asphalt, stirring at high speed and uniformly, and adding deionized water to control the solid content of the obtained dispersion to be within the range of 10 to 15wt.%; the solid content of the water-based asphalt is 50wt.%, and the vacuum carbonization residual carbon content is 50wt.%; 3) spray drying the dispersion obtained in step 2) using a spray dryer to obtain a dry powder; the spray inlet temperature of the spray dryer is 200-220° C., and the feed rate is 20-30 kg / h; 4) weighing aluminum metaphosphate powder according to the formula ratio, adding it to the dry powder in step 3), mixing evenly, adding it to a mechanical fusion machine for fusion, and obtaining a precursor with a layer of asphalt and aluminum metaphosphate modified on the surface; 5) The precursor in step 4) is transferred to a vacuum furnace for high-temperature carbonization, and then taken out, crushed and sieved to obtain a nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface; the high-temperature carbonization temperature is 800-1200° C., and the time is 3-6 hours; The aluminum metaphosphate is dispersed in the carbon coating layer to enhance the peeling strength of the carbon coating layer.
2. The nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface according to claim 1, characterized in that: The content of the aluminum metaphosphate composite modification layer is 4-10wt.%.
3. Use of the nano-silicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface as described in claims 1 to 2 in lithium-ion batteries.
4. The use according to claim 3, characterized in that: The lithium ion battery comprises a button-type lithium ion battery.
5. A button-type lithium-ion battery, characterized in that: The negative electrode material comprises the nano silicon-graphite composite negative electrode material with carbon coating and aluminum metaphosphate composite modification layer on the surface as described in claims 1-2.
6. The button-type lithium-ion battery according to claim 5, characterized in that: At a current density of 100 mA / g, the button-type lithium-ion battery has an initial discharge capacity of 633.2 to 671.6 mAh / g, an initial reversible charge capacity of 532.1 to 555.8 mAh / g, a reversible capacity of 483.9 to 580.2 after 300 cycles, and a retention rate of 98.8 to 104.4%.